Effect of admixtures on the corrosion of reinforced concrete structures - Velásquez, Ricardo; Acosta, María; Gaona, Citlalli; Almeraya, Facundo; Martínez, Alberto (Revista Ingeniería de Construcción, 2004)
This paper aims at determining the influence of additives in the corrosion of reinforced concrete structures by using electrochemical techniques. Their influence on the mechanical properties is determined . The authors perfomed chemical analyses of the additives, characterizing the steel measure the pH, and evaluat the compressive and flexural strength of the concrete, the porosity and water absorption. The methodology was carried out according to ASTM and ACI standards. The action of the admixtures was evaluated and their effects on the corrosion of reinforced concrete were measured using corrosion potentials and corrosion rates. The carbonatation and penetration of chlorides was also determined. The study was suplemented by a morphologic characterization using a scanning electron microscope. Specimens with and without reinforcement were elaborated, three of each were tested for obtaining an average. Prismatic specimens without reinforcement were also cast with the following chemical additives: Air-entraining, plasticizers, retardants, accelerating, coloring and fly ash. After curing, they were exposed to an aggressive atmosphere with sodium chloride. The corrosion potential in accordance to ASTM C876 standard, revealed that cylinders had corrosion, and the rate corrosion of the cylinders exposed in sodium chloride corresponds a of moderate corrosion degree.